Language development and social interaction in blind children - Pérez-Pereira, Miguel (Psychology Press and Routledge classic editions, 2020)
The Classic Edition of this foundational text includes a new preface from Miguel Prez-Pereira, examining how the field has developed since first publication. The volume provides an in-depth account of blind children's developing communicative abilities, with particular emphasis on social cognition and language acquisition from infancy to early school age. It provides insights into why the development of blind children may differ from that of sighted children and explores development of "theory of mind" and perspective taking in language learning. It also discusses the caregiver-child interaction, research on early intervention and practical strategies for blind children that can assist parents and practitioners. The up-to-date preface discusses recent neurological research and the comparison between the psychological development of visually impaired and autistic children. Language Development and Social Interaction in Blind Children continues to facilitate dialogue between those interested in the study of typically developing children and those interested in the development of children who are blind, and challenges some widelyheld beliefs about the development of communication in blind children